A multidisciplinary team evaluation of management guidelines for adult short bowel syndrome. (April 2023) - Wall, Elizabeth; Catron, Hilary; Delgado, Adela; Greif, Sophie; Herlitz, Jean; Moccia, Lisa; Lozano, Edward; Mercer, David; Vanuytsel, Tim; Berner-Hansen, Mark; Lakananurak, Narisorn; Gramlich, Leah
Summary: Background & aims: An international, multidisciplinary management working group (MWG) convened to review clinically useful short bowel syndrome (SBS) literature and identify gaps and inconsistencies in the management of adults with SBS. Methods: Using nominal group technique for literature review, key publications were identified, discussed, and ranked by importance related to management of SBS. Gaps in management recommendations for SBS were identified upon critical review of the selected publications. Results: Five guidelines, seven review articles, one series of six articles, and one single center series were selected and prioritized for their importance to SBS management. Evaluation of the articles by the MWG identified ten gaps and opportunities to standardize and improve SBS management. Conclusion: The main practice areas in need of more definitive guidelines are the management of high stool output and strategies to improve absorption of medications, nutrients, and fluids. An understanding of current real-world clinical practices related to these gaps could allow for development of best practice standards and improve patient-focused care.